Pembobolan Bank Melalui Transaksi Letter of Credit L/C - Pelupessy, Eddy; Hamonangan, Sobardo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research is entitled Bank Break-In Through Letter Of Credit L/C Transactions. The type of research used is normative juridical, namely to examine legal concepts related to law enforcement for misuse of letters of credit as a means of payment in transactions. The results of the study revealed that the presence of fictitious documents as a means of disbursing L/C clearly contains evil motives coloring bank break-ins, as a bank that is involved in the international trade area (International track Jurvice), operational risks have certainly been calculated in advance. Risk Management should understand the potential risks. The risks that can occur in connection with the involvement of the bank as a guarantor and mediator between sellers and buyers from different countries. Of course it is also riskier to provide dual facilities to one customer as an importer and exporter customer at the same time. Therefore, law enforcement for misuse of letters of credit is the application of the principle of knowing the customer which is the embryo of the principle of maximum caution in order to minimize crime in the banking sector.